Endothelial cell dysfunction: a key determinant for the outcome of allogeneic stem cell transplantation - Luft, Thomas; Dreger, Peter; Radujković, Aleksandar (Bone marrow transplantation, 2021)
Abstract - Allogeneic hematopoietic stem cell transplantation (alloSCT) carries the promise of cure for many malignant and non-malignant diseases of the lympho-hematopoietic system. Although outcome has improved considerably since the pioneering Seattle achievements more than 5 decades ago, non-relapse mortality (NRM) remains a major burden of alloSCT. There is increasing evidence that endothelial dysfunction is involved in many of the life-threatening complications of alloSCT, such as sinusoidal obstruction syndrome/venoocclusive disease, transplant-associated thrombotic microangiopathy, and refractory acute graft-versus host disease. This review delineates the role of the endothelium in severe complications after alloSCT and describes the current status of search for biomarkers predicting endothelial complications, including markers of endothelial vulnerability and markers of endothelial injury. Finally, implications of our current understanding of transplant-associated endothelial pathology for prevention and management of complications after alloSCT are discussed.
Gesehen am 03.07.2023